The Effectiveness of Premarital Education Using the Interpersonal Awareness and Choice Method on Marital Stability and Emotional Expressiveness - Sobhaninia, Amirhossein; Golpour, Karim; Reyhani, Atefeh; Hoseinkhani , Ali (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the effectiveness of premarital education based on the Interpersonal Awareness and Choice Method in enhancing marital stability and emotional expressiveness among engaged couples.Methods and Materials: A randomized controlled trial design was used involving 30 participants recruited from premarital counseling centers in Tehran. Participants were randomly assigned to an experimental group (n = 15), which received a ten-session premarital education program, and a control group (n = 15), which received no intervention during the study period. The intervention was delivered in weekly 60-minute group sessions focusing on interpersonal awareness, emotional literacy, and decision-making in romantic relationships. Standardized instruments were used to measure marital stability and emotional expressiveness at three time points: pretest, posttest, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-27 to assess within-group and between-group differences over time.Findings: Results indicated a significant interaction effect between time and group for marital stability (F(2, 56) = 14.72, p < 0.001, η² = 0.34), with the experimental group showing greater improvements compared to the control group. Similarly, emotional expressiveness demonstrated a significant group-by-time interaction (F(2, 56) = 17.59, p < 0.001, η² = 0.38), with post-hoc comparisons revealing that the experimental group had significantly higher scores at both posttest and follow-up phases. All assumptions for repeated measures ANOVA were confirmed prior to analysis.Conclusion: The findings suggest that premarital education based on the Interpersonal Awareness and Choice Method is an effective intervention for promoting emotional expressiveness and marital stability among engaged individuals. These results highlight the value of incorporating structured emotional and interpersonal training into premarital counseling services to support relationship resilience and long-term satisfaction.Keywords: Premarital education, interpersonal awareness, emotional expressiveness, marital stability.